PENGARUH LOCUS OF CONTROL DAN ENVIRONMENTAL RISK FACTORS TERHADAP KINERJA AUDITOR PEMERINTAH DALAM MELAKSANAKAN AUDIT PEMERINTAHAN (STUDI KASUS PADA BPKP PROPINSI LAMPUNG) - Einde Evana; Denny Kassan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2009)
This study purposed to understand the effect of locus of control and environmental risk factors to financial and development monitoring board (Badan Pengawasan Keuangan dan Pembangunan/BPKP) Lampung province. Sampling method used in this study is purposive judgment sampling method. Data collected by interviewing method and sending guestionnaire directly to respondent. From 100 guestionnaires, 62 guestionnaires returned egual to 62% return rate. Analysis method used in this study is double linear regression by SPSS (Statistical Package for The Social Science). The result shows that Jocus of control an environmental risk factors partially have positive and significant effect to the performance of governmen internal auditor. Partial testing used t-count at 95% of certainty rate and at 5%. Result of hypothesis testing simultaneously shows that locus of control and environmental risk factors variable positively and significantly influence the performance of government internal auditor. Hypothesis testing towards regression coefficient simultaneously used by F-test at 0,228 means that 22,8% of government internal auditor performance can be explained by second variation of independent variable in this study.